Phase IV Prospective Clinical Study to Evaluate the Effect of Taurine on Liver Function in Postsurgical Adult Patients Requiring Parenteral Nutrition. (14th May 2014) - Arrieta, Francisco; Balsa, José Antonio; de la Puerta, Cristina; Botella, José Ignacio; Zamarrón, Isabel; Elías, Elena; del Río, José Ignacio Pérez; Alonso, Paloma; Candela, Ángel; Blanco‐Colio, Luis Miguel; Egido, Jesús; Navarro, Pilar; et al.
Abstract : Background: Taurine's role in bile acid metabolism and anti‐inflammatory activity could exert a protective effect on hepatobiliary complications associated with parenteral nutrition (PN). In this study, the effects of 2 amino acid solutions, with and without taurine, on liver function administered to nonacutely ill postsurgical patients as part of a short‐term PN regimen were prospectively compared. Methods : Adult patients randomly received (double‐blind) Tauramin 10% or a standard PN solution without taurine as the control (1.5 g amino acid/kg body weight [bw]/d; infusion rate of ≤4 mg glucose/kg bw/d) for a period of 5–30 days. γ‐Glutamyl transpeptidase (GGT) and other indicators of liver function, glucose metabolism, lipid profile, inflammation markers, and treatment safety data were collected. Results : Thirty‐five patients receiving taurine PN and 39 receiving control PN were enrolled (intention‐to‐treat [ITT] population). Most patients (n = 62) discontinued after day 7 of follow‐up (per‐protocol [PP] population: n = 24 and n = 27, respectively). ITT patients with high GGT values after 5 days of PN comprised 68.6% and 64.1%, respectively. The mean change in GGT values with respect to the baseline values was 167 ± 192 and 157 ± 185 IU/L, respectively. Low‐density lipoprotein (LDL) cholesterol levels after 7 days of PN were significantly decreased in the taurine PN group of PP patients (–2.83 ± 30.9 vs 23.9 ± 27.0 mg/dL for control PN; P < .05). None of the adverse events reported (taurine PN: n = 6; control PN: n = 7) were treatment related. Conclusion : PN solutions with and without taurine had similar effects on liver function parameters, except for an LDL reduction in PN with taurine, when administered to nonacutely ill postsurgical patients in the short term (5–7 days).